Dissolution rate and bioavailability enhancement of co-ground mixtures of paliperidone, with different hydrophilic carriers - Pandey, Anuja; Rath, Bhabagrahi; Dwivedi, Anil Kumar (International Current Pharmaceutical Journal, 2013)
Co-ground mixtures of poorly water soluble drug Paliperidone (PAL) with different hydrophilic carriers [Polyvinylpyrrolidine (Plasdone K-25 and Plasdone S-630), Hydroxypropyl methyl cellulose (HPMC), Hydroxypropylcellulose (HPC) and Sodium alginate were prepared to improve the dissolution rate of PAL. Co-grinding with PVP, especially with PVP- S630 (Vinyl pyrrolidone/ vinyl acetate co-polymer), was more effective in reduction of particle size than milling of drug alone. DSC studies indicated that crystalline nature of drug was reduced after co-grinding with PVP grades as compared to their corresponding physical mixtures. The hydrophilic carriers other than PVP did not reduce the crystalline nature of the drug significantly. X-ray diffraction (XRD) was carried out for selected batches to confirm DSC results. Significant enhancement in dissolution rate as well as extent was observed with co-ground mixtures of drug and PVP. Among all the prepared batches in this study, co-ground mixture of PAL and Plasdone S-630 in 1:1 ratio showed best results in terms of extent of dissolution as well as dissolution rate in water. This effect was not only due to particle size reduction, but also loss of crystalline nature of the drug during co-grinding. PVP was found to be a better carrier among the different hydrophilic carriers used in the study for improving the dissolution characteristics of PAL. The extent of the mean plasma exposures of PAL was 7-fold higher in animals treated with co-ground mixture of PAL, Plasdone S630 (1:1) compared to animals treated with Pure PAL. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13632 International Current Pharmaceutical Journal, February 2013, 2(3): 70-77